MANAGEMENT FRAMEWORKS FOR AI-INTEGRATED CREATIVE INDUSTRIES - Dhabliya, Dharmesh; Rani, Jyoti; Gupta, Kumod Kumar; Singh, Dukhbhanjan; Feriooz, Aadil; Hosamani, Suma Sidramappa; Tewatia, Nidhi (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Implementing Artificial Intelligence (AI) into creative sectors is a radical change of how art, media, and design systems work. This study suggests an overall management system that integrates AI-based innovation with conventional creative processes. The paper starts with an account of the history of management paradigms in the field of creativity, with a particular focus on the digital transformation and computational creativity as the factors that transformed the way of how organizations are run. The analysis of literature provides a solid understanding of the models of AI integration that are available to date, and there are gaps in governance, ethical implementation, and interdisciplinary cooperation. The study applies the mixed-method design, i.e., the qualitative data offered by industry participants and quantitative evaluation of the performance of the AI-based workflow, to meet the requirements of the empirical rigor and the reliability of the framework. The framework suggested has two structural levels: strategic levels, which cover governance, innovation and collaboration, and operational levels, which cover automation, co-creation and content optimization. These aspects are created to accommodate adaptability management practices that promote creativity without sacrificing humanism. The case studies of implementation in the areas of media, advertising, design, and music industry already reveal the levels of variable AI maturity, providing a comparative insight into the area of scalability and efficiency.